2019
DOI: 10.1142/s2194565919500192
|View full text |Cite
|
Sign up to set email alerts
|

The Market for Cryptocurrency: How Will It Evolve?

Abstract: This study examines the concept of cryptocurrency and gives a brief history and overview of its characteristics. In an increasingly electronic society, cryptocurrency could be the next step in the evolution of finance in the same way that the internet was a step in the evolution of communication. In the coming years, countries may even announce the release of national cryptocurrencies, although certain conditions must be met for these efforts to be successful. Although the market is still in the early stages, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Just like the internet was a milestone in the growth of communication, cryptocurrency could be the subsequent move in the evolution of finance in this growing electronic era. According to Allen and Bryant (2019) , cryptocurrency is the obvious next step in the evolution of currency in a culture that is becoming more electronic, digital, and virtual every day. Although cryptocurrency and its innate technology will become more accessible and useful in the future, it is currently a highly divisive issue ( Allen and Bryant, 2019 ).…”
Section: Evolution Of Cryptocurrenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Just like the internet was a milestone in the growth of communication, cryptocurrency could be the subsequent move in the evolution of finance in this growing electronic era. According to Allen and Bryant (2019) , cryptocurrency is the obvious next step in the evolution of currency in a culture that is becoming more electronic, digital, and virtual every day. Although cryptocurrency and its innate technology will become more accessible and useful in the future, it is currently a highly divisive issue ( Allen and Bryant, 2019 ).…”
Section: Evolution Of Cryptocurrenciesmentioning
confidence: 99%
“…According to Allen and Bryant (2019) , cryptocurrency is the obvious next step in the evolution of currency in a culture that is becoming more electronic, digital, and virtual every day. Although cryptocurrency and its innate technology will become more accessible and useful in the future, it is currently a highly divisive issue ( Allen and Bryant, 2019 ). Although this part is not directly related to our work, it may provide readers with useful information about the history of cryptocurrency.…”
Section: Evolution Of Cryptocurrenciesmentioning
confidence: 99%
“…According to Coin Telegraph, despite numerous statements by the Tether organization, there is serious doubt by members of the community that everything is legitimate [ 40 ]. Allen and Bryant [ 41 ] concluded that although the idea about introducing Tether is great in theory, and something like Tether may be the first step in widespread cryptocurrency adoption, it may need to come from an organization that is more trusted for innovation in space. Although extremely unlikely, if Tether were to become officially backed by the U.S. government, the issue some may have with trust could be resolved.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on behavioral finance, if the investor sentiments caused by speculative needs and subjective performance influence the investment demand, asset prices will diverge from their value (Ji et al , 2020), which is also confirmed by empirical research (Ba and Zhu, 2016; Wei-qi and Xin-xin, 2014). Blockchain is developing so rapidly (Ji et al , 2020), so as the cryptocurrencies (Allen and Bryant, 2019) can influence the general sentiment toward firms that use this technology (Ji et al , 2020) and cryptocurrencies. In addition, both these technology firms and cryptocurrencies are backed by blockchains.…”
Section: Introductionmentioning
confidence: 99%